2016
DOI: 10.1098/rsob.160149
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide signals are interlinked with calcium signals in normal pancreatic stellate cells upon oxidative stress and inflammation

Abstract: The mammalian diffuse stellate cell system comprises retinoid-storing cells capable of remarkable transformations from a quiescent to an activated myofibroblast-like phenotype. Activated pancreatic stellate cells (PSCs) attract attention owing to the pivotal role they play in development of tissue fibrosis in chronic pancreatitis and pancreatic cancer. However, little is known about the actual role of PSCs in the normal pancreas. These enigmatic cells have recently been shown to respond to physiological stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 60 publications
(105 reference statements)
1
65
1
Order By: Relevance
“…These results may indicate the existence of a further necrotic amplification loop in which initial damage to PACs, induced – for example – by FAEEs or a bile acid, causes release of activated trypsin from dying PACs, which in turn activates PSCs to produce Ca 2+ signals, generating NO that may diffuse into neighbouring PACs, thereby causing further cell death (Jakubowska et al . ) and therefore further liberation of trypsin and other proteases (Fig. ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results may indicate the existence of a further necrotic amplification loop in which initial damage to PACs, induced – for example – by FAEEs or a bile acid, causes release of activated trypsin from dying PACs, which in turn activates PSCs to produce Ca 2+ signals, generating NO that may diffuse into neighbouring PACs, thereby causing further cell death (Jakubowska et al . ) and therefore further liberation of trypsin and other proteases (Fig. ).…”
Section: Discussionmentioning
confidence: 99%
“…These Ca 2+ signals – via NO formation in PSCs and with NO diffusing into adjacent PACs (Jakubowska et al . ) – would contribute to further damage of PACs, which in turn would cause further release of kallikrein leading to a further increase in the BK level and thereby further stimulation of PSCs acting to promote PAC necrosis. We have shown that pharmacological inhibition of NO synthase provides remarkable protection against necrosis (Jakubowska et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KRAS signaling via paracrine signaling promotes a fibro-inflammatory microenvironment by stimulating fibroblasts, PSCs and immune cells [51, 53]. In addition, external stressors that cause activation of PSCs include hypoxia, hyperglycemia, alcohol and metabolites, oxidative stress inducing agents like hydrogen peroxide and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase which is a source of reactive oxygen species (ROS) [51, 52, 55]. Activated PSCs can remain in a perpetually active state secreting a number of factors including ECM proteins (collagen, FN, and laminin), cytokines (like TGF-β, IL-1, IL-8, and IL-15), connective tissue growth factor (CTGF), monocyte chemoattractant protein-1 (MCP-1), and matrix metalloproteinase-2 (MMP-2) that can perpetuate PSCs themselves or mediate their effects on cancer cells [52].…”
Section: Pathobiology and Disease Progressionmentioning
confidence: 99%